Penerapan Model pembelajaran Cooperative Integrated Reading and Composition (CIRC) Untuk Meningkatkan Kemampuan Siswa Menemukan Informasi Baru Pada Teks Non Fiksi Melalui Pada Siswa Kelas IV UPTD SD Negeri 11 Jangka - Zulkarnaini, Zulkarnaini; Aria, Rizki; Evendi, Evendi (Universitas Pahlawan Tuanku Tambusai, 2024)
Students' ability to extract information from nonfiction texts is still a challenge at the elementary school level, which is characterized by students' low ability to find information in nonfiction texts that are read. The purpose of the study was to improve students' ability to understand and find information from nonfiction texts. The research method used was classroom action research (CAR) with two cycles of implementation. The subjects of the study were 18 fourth grade students of SD Negeri 11 Jangka. Data were collected through tests, observations, and interviews. The results showed that the application of the CIRC model significantly improved students' understanding of nonfiction texts. Before the application of the model, the student completion rate only reached 39%, then increased to 72% in cycle II, and reached 89% in cycle II. In addition, student activity and teacher involvement in learning also increased significantly. The results showed that the CIRC model can be an effective strategy in improving students' reading comprehension skills in elementary schools.